Baudelaire's world - Lloyd, Rosemary 1949- (Cornell University Press, 2018)
Charles Baudelaire is often regarded as the founder of modernist poetry. Written with clarity and verve, Baudelaire's World provides English-language readers with the biographical, historical, and cultural contexts that will lead to a fuller understanding and enjoyment of the great French poet's work.Rosemary Lloyd considers all of Baudelaire's writing, including his criticism, theory, and letters, as well as poetry. In doing so, she sets the poems themselves in a richer context, in a landscape of real places populated with actual people. She shows how Baudelaire's poetry was marked by the influence of the writers and artists who preceded him or were his contemporaries. Lloyd builds an image of Baudelaire's world around major themes of his writing—childhood, women, reading, the city, dreams, art, nature, death. Throughout, she finds that his words and themes echo the historical and physical realities of life in mid-nineteenth-century Paris. Lloyd also explores the possibilities and limitations of translation. As an integral part of her treatment of the life, poetry, and letters of her subject, she also reflects on published translations of Baudelaire's work and offers some of her own translations